Effect of Strategic Determinants of Training on the Job Performance, Effectiveness and Efficiency: An Empirical Study (Malaysian Management Journal, 2012)
Investments in the development of human capital, which are concerned with the development of knowledge, competencies and qualifications of employees, are considered more important today for the performance of an organization and for the economic growth of a country than investments in physical capital. Keeping this in perspective, this research examined the effect of the determinants of training such as training and development, strategic objective, culture and value, knowledge and skills, rewards and promotion, readiness and flexibility on job performance, effectiveness, and efficiency of employees in a large service conglomerate. The results indicated significant positive relationship of training and development, strategic objectives, culture and values, knowledge and skills, rewards and promotion with job performance, effectiveness, and efficiency of employees. The study also reported the importance of training, strategic objective, culture and value, knowledge and skills, rewards and promotion to augment job performance, effectiveness and efficiency but undermined the significance of readiness and flexibility. The employees underpin motivational factors that are responsible for better job performance. The findings suggest that harnessing all these determinants may render service organizations with the potential to foster job performance, effectiveness, and efficiency of employees.